Scheme of intermittent fasting and reduction of anthropometric measures, lipid profile, blood pressure and cardiovascular risk: Esquema de ayuno intermitente y reducción de medidas antropométricas, perfil lipídico, presión arterial y riesgo cardiovascular - Wong–Gonzales, Javier (2021)
Introduction: Lifestyle is a fundamental role in the risk of cardiovascular diseases and chronic diseases. Objective: To evaluate the effect of the 16/8 intermittent fasting scheme against anthropometric measurements, lipid profile values, blood pressure ​​and cardiovascular risk. Method: Longitudinal analytical study with intervention. Fifteen patients treated in the nutrition area in a private center between January and October 2020 submitted to the 16/8 intermittent fasting scheme for four months, seeking to reduce anthropometric measurements, lipid profile, blood pressure and / or cardiovascular risk. Variables: body weight, body mass index (BMI), waist-hip index (WHI), abdominal circumference, lipid profile, cardiovascular risk according to Framingham (Framingham AMR B table), total cholesterol / HDL and LDL / HDL indices. Results: The average age was 47.1 years, the average height was 1.66 m., The average body weight was 84.3 Kg., The average of the BMI was 30.46, the average of the WHI was 0.94, the average of the abdominal circumference was 99.87, the mean total cholesterol, HDL and LDL were 240.06, 43.73 and 153.2 respectively, the mean cardiovascular risk according to Framingham was 0.11% and the mean total cholesterol / HDL and LDL / HDL indices were 5.88 and 3.69. The evaluation of averages before and after found significant differences (p <0.05) at 3 and 4 months of evaluation. Conclusions: The intermittent fasting scheme showed a significant reduction in anthropometric measurements, lipid profile and cardiovascular risk. Additionally, an increase in HDL was observed.